Survival and Clinical Outcomes in Patients with Metastatic Epidural Spinal Cord Compression: Results from the AOSpine Prospective Multi-Centre Study of 142 patients. Issue 1 (April 2016) - Fehlings, Michael; Nater, Anick; Tetreault, Lindsay; Kopjar, Branko; Arnold, Paul; Dekutoski, Mark; Finkelstein, Joel; Fisher, Charles; France, John; Gokaslan, Ziya; Rhines, Laurence; Rose, Peter; et al.
Introduction: Although surgery is being increasingly used in patients with Metastatic Epidural Spinal Cord Compression (MESCC) as a complementary strategy to radiation and chemotherapy, the impact of surgery on quality of life (QoL) is not well established. This study aimed to prospectively evaluate survival, neurological, functional, and QoL outcomes in MESCC patients undergoing operative management. Material and Methods: A total of 142 surgically treated patients with a single symptomatic MESCC lesion enrolled in a prospective North American multi-center study were followed for 12 months. Clinical data, such as Brief Pain Inventory (BPI), ASIA, SF-36, Oswestry Disability Index (ODI), and EQ-5D scores, were obtained both pre- and post-operatively. Results: The median survival was 7.7 months. The 30-day and 12-month mortality rates were 9% and 62%, respectively. Six weeks post-operatively, ambulatory status ( p  = 0.02) and bladder control ( p  = 0.03) were significantly improved. Overall, 67.5% of ASIA B, C, or D patients gained at least 1 grade after surgery, 25% remained stable, and 7.5% deteriorated. ODI, EQ-5D, BPI scores were significantly improved at each follow-up (p ≤ 0.01). SF-36 scores were generally higher after surgery for mental and physical components, and for all domains except energy/fatigue. The incidence of wound complications was 10% and 2 patients required a second surgery (screw malposition and epidural hematoma). Conclusion: Surgical intervention, as a complementary adjunct to radiation and chemotherapy, provides immediate and sustained improvement in pain, neurological, functional, and QoL outcomes with acceptable risks in patients with a focal symptomatic MESCC lesion.